Erythropoietin Signaling Increases Choroidal Macrophages and Cytokine Expression, and Exacerbates Choroidal Neovascularization - Bretz, Colin A; Divoky, Vladimir; Prchal, Josef; Kunz, Eric; Simmons, Aaron B; Wang, Haibo; Hartnett, Mary Elizabeth (Scientific reports, 2018)
Erythropoietin (EPO) is recognized for neuroprotective and angiogenic effects and has been associated with aging and neovascular age-related macular degeneration (AMD). We hypothesized that systemic EPO facilitates the development of choroidal neovascularization (CNV). Wild type mice expressed murine EPOR (mWtEPOR) in RPE/choroids at baseline and had significantly increased serum EPO after laser treatment. To test the role of EPO signaling, we used human EPOR knock-in mice with the mWtEPOR gene replaced by either the human EPOR gene (hWtEPOR) or a mutated human EPOR gene (hMtEPOR) in a laser-induced choroidal neovascularization (LCNV) model. Loss-of-function hWtEPOR mice have reduced downstream activation, whereas gain-of-function hMtEPOR mice have increased EPOR signaling. Compared to littermate controls (mWtEPOR), hMtEPOR with increased EPOR signaling developed larger CNV lesions. At baseline, hMtEPOR mice had increased numbers of macrophages, greater expression of macrophage markers F4/80 and CD206, and following laser injury, had greater expression of cytokines CCL2, CXCL10, CCL22, IL-6, and IL-10 than mWtEPOR controls. These data support a hypothesis that injury from age- and AMD-related changes in the RPE/choroid leads to choroidal neovascularization through EPOR-mediated cytokine production.
Keywords: Animals; choroidea; Receptors, Erythropoietin; Female; Cytokines; neovaskularizace choroidey; makrofágy; ženské pohlaví; Mice, Knockout; myši knockoutované; cytokiny; Macrophages; Mice; Erythropoietin; signální transdukce; kultivované buňky; myši; Signal Transduction; erythropoetin; Cells, Cultured; Choroidal Neovascularization; Male; modely nemocí na zvířatech; Choroid; receptory erythropoetinu; Disease Models, Animal; zvířata; mužské pohlaví; Mice, Inbred C57BL; myši inbrední C57BL